2010
DOI: 10.1136/adc.2010.194993
|View full text |Cite
|
Sign up to set email alerts
|

Klebsiella brain abscess in a neonate

Abstract: Klebsiella pneumoniae is rarely associated with neonatal cerebral abscess. A case of Klebsiella brain abscess in a neonate is described. Diagnosis of abscess was confirmed by magnetic resonance imaging and ultrasound-guided aspiration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…The clinical symptoms of brain abscess vary due to different virulence of pathogenic bacteria and the body's response to different conditions, which may easily lead to misdiagnosis, thus resulting in poor prognosis and an increased risk of mortality in children. Even if they survive, there will be permanent neurological impairment [3][4][5][6][7][8][9][10][11] . Therefore, in addition to the prevention of brain abscess, diagnosing and treating it early are essential.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The clinical symptoms of brain abscess vary due to different virulence of pathogenic bacteria and the body's response to different conditions, which may easily lead to misdiagnosis, thus resulting in poor prognosis and an increased risk of mortality in children. Even if they survive, there will be permanent neurological impairment [3][4][5][6][7][8][9][10][11] . Therefore, in addition to the prevention of brain abscess, diagnosing and treating it early are essential.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Brain ultrasound and CT scan are appropriate tools for the diagnosis of neonatal brain abscess and also for follow up after beginning the treatment [5,6]. MR imaging has a high sensitivity and specificity in detecting brain abscesses but is less utilized due to enough diagnostic information derived from ultrasound and CT Scan studies [2].…”
Section: Introductionmentioning
confidence: 99%
“…Brain abscesses in the infant population are exceedingly rare and occur as an uncommon complication of meningitis or sepsis [1][2][3][4][5][6]. A study at Children's Hospital Boston showed that congenital heart disease was the most common predisposing factor particularly in older children [1].…”
Section: Introduction mentioning
confidence: 99%
“…A study at Children's Hospital Boston showed that congenital heart disease was the most common predisposing factor particularly in older children [1]. Commonly, organisms such as Citrobacter and Proteus are involved and abscesses are often large and multiple [2,3]. The frontoparietal region of the brain appears to be most common location, particularly after hematogenous ___________________________________________ dissemination and lesions are often found around the ventricles [3].…”
Section: Introduction mentioning
confidence: 99%